Analysis on Lighweighting Approach Topology Optimization Design for Additive Manufacturing (DfAM) - Ismail, Muhammad Ikmal; Ibrahim, Mustaffa (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In order to produce a lightweight and high-performance configuration that are difficult to achieve with traditional concepts, topology optimization was developed as an advanced structural design technique. Earlier topology optimization developments considered traditional manufacturing methods with limitations in the processing of complex geometries. However, with the emergence of additive manufacturing technologies, the technology that builds a part layer on a layer directly from the part’s three-dimensional (3D) model data, it is no longer a problem to produce complex shape geometry in order to reduce the weight. The analysis from the study enable to determine the analysis on lighweighting approach topology optimization design for Additive Manufacturing (DfAM) while maintaining its overall performance. The mechanical properties can be determined by using Altair Inspire 2019 where the software can design the model and use Finite Element Method to solve the analysis. The weight that being reduce from the original model which is 60 percent above. There are three types of topology optimization that being applied which is Topology, Latticing and Combination of Topology and Lattice. It is found that by reduce its weight and volume by topology which is 80% reduction with safety factor of 1.2 meanwhile latticing 88.79% reduction with safety factor of 2 and combination of topology and lattice 92.39% mass reduction with safety factor of 1.7 which show all model still can fulfil its mechanical properties and maintain its overall performance.